2013
DOI: 10.3109/00016357.2012.741699
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of incorporating nanosilver/nanohydroxyapatite particles on the shear bond strength of orthodontic adhesives

Abstract: Incorporation of silver/HA nanoparticles containing 5% and 1% silver maintains and increases the SBS of orthodontic adhesives, respectively, whereas increasing the amount of particles to 10% has an undesirable effect when compared to the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 15 publications
10
71
1
1
Order By: Relevance
“…In the present study, the shear bond strengths ranged from 13.1 to 14.6 MPa. Other previous studies using commercial orthodontic adhesive reported similar shear bond strengths values (Pithon et al 2007; Akhavan et al 2013). Hence, the new antibacterial DMADDM-containing orthodontic bracket cement of the present study with 3% DMADDM appeared to yield an adequate orthodontic bond strength to enamel.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In the present study, the shear bond strengths ranged from 13.1 to 14.6 MPa. Other previous studies using commercial orthodontic adhesive reported similar shear bond strengths values (Pithon et al 2007; Akhavan et al 2013). Hence, the new antibacterial DMADDM-containing orthodontic bracket cement of the present study with 3% DMADDM appeared to yield an adequate orthodontic bond strength to enamel.…”
Section: Discussionsupporting
confidence: 71%
“…Orthodontic bonding agents are in direct contact with the vulnerable enamel surface and their properties with respect to bacterial adhesion may play a key role on prevention of the starting process of net mineral loss. Preceding reports have suggested the incorporation of antibacterial agents such as nanosilver and nanohydroxyapatite into orthodontic cements to combat cariogenic biofilm (Ahn et al 2009; Akhavan et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Akhavan et al demonstrated that incorporating AgNPs into orthodontic adhesives could increase or maintain the shear bond strength of an orthodontic adhesive while simultaneously increasing its resistance to bacteria [110]. A recent study by Chladek et al found that incorporating AgNPs into dental composites could reduce the microbial colonization of lining materials, enhancing the antifungal efficiency [111].…”
Section: Dentistrymentioning
confidence: 99%
“…Various load particles have been added to dental adhesives to strengthen the link of bond strength to the dental structure, diminishing polymerization shrinking and increasing the modulus of elasticity of the adhesive layer [12]. Recently, load nanoparticles [13][14][15][16], especially nanoparticles of ceramic materials [15,16], have been used in the formulation of composites, with the purpose of improving physical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%